Training on Village Website Management for Village Officials in Manimbahoi Village, Parigi District, Gowa Regency as Data Literacy Education: Pelatihan Pengelolaan Website Desa untuk Aparat Desa di Desa Manimbahoi, Kecamatan Parigi, Kabupaten Gowa sebagai Edukasi Literasi Data - Ahmar, Ansari Saleh; Rais, Zulkifli; Iskandar, Akbar (Mattawang: Jurnal Pengabdian Masyarakat, 2023)
The training was held in the Meeting Room of Manimbahoi Village, Parigi District, Gowa Regency, South Sulawesi Province on August 6, 2023. The participants of the training were Manimbahoi Village officials, with the aim of understanding the importance of data to be published and also as an effort to educate village officials regarding data literacy. This service activity for Manimbahoi Village officials, in an effort to educate data literacy, runs smoothly, as expected. This can be seen from the increase in the ability and knowledge of village officials from not knowing about website management and publishing village news. Using this knowledge, village data can be published on village websites. Abstrak Pelatihan ini dilaksanakan di Ruang Pertemuan Desa Manimbahoi, Kecamatan Parigi, Kabupaten Gowa, Provinsi Sulawesi Selatan pada tanggal 6 Agustus 2023. Peserta dari pelatihan ini adalah aparat Desa Manimbahoi, dengan tujuan agar aparat desa tersebut paham mengenai pentingnya data untuk dipublikasikan dan juga sebagai upaya untuk edukasi aparat desa terkait literasi data. Kegiatan pengabdian untuk aparat Desa Manimbahoi ini sebagai upaya untuk edukasi literasi data berjalan lancer dan sesuai dengan yang diharapkan. Hal ini terlihat terjadinya peningkatan kemampuan dan pengetahuan aparat desa dari tidak tahu menjadi tahu pengelolaan website dan penerbitan berita desa. Dengan adanya pengetahuan ini maka data-data desa dapat dipublikasikan di website desa.